2022
DOI: 10.3390/pr10050928
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristic of High-Speed Centrifugal Refrigeration Compressor with Different Refrigerants via CFD Simulation

Abstract: This study used Computational Fluid Dynamics (CFD) to simulate and analyze the working fluid in magnetic centrifugal refrigerant compressors using R-134a to mixed refrigerant: R-513A and HFO (Hydrofluoroolefins) Hydrofluoroolefin refrigerant: R-1234yf, and the impact on integrated part-load performance, Integrated Part Load Value (IPLV) and internal flow field. This study used a single-stage 280 USRT maglev centrifugal refrigerant compressor as a simulation model. Three different refrigerants were used: R-134a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Hung et al [1] investigated the integrated part-load performance, integrated part load value (IPLV) and internal flow field of the magnetic centrifugal refrigerant compressors with different refrigerants, such as R-134a, R-513A and R-1234yf, as working fluids using the computational fluid dynamics technique. Their results showed that the maglev centrifugal refrigerant compressor efficiency appreciably dropped as the original refrigerant R-134a was replaced by R-513A and R-1234yf.…”
Section: Characteristics Of the Modern Refrigerantsmentioning
confidence: 99%
“…Hung et al [1] investigated the integrated part-load performance, integrated part load value (IPLV) and internal flow field of the magnetic centrifugal refrigerant compressors with different refrigerants, such as R-134a, R-513A and R-1234yf, as working fluids using the computational fluid dynamics technique. Their results showed that the maglev centrifugal refrigerant compressor efficiency appreciably dropped as the original refrigerant R-134a was replaced by R-513A and R-1234yf.…”
Section: Characteristics Of the Modern Refrigerantsmentioning
confidence: 99%